PENDIDIKAN TOLERANSI LINTAS AGAMA (STRATEGI TOKOH AGAMA DALAM MENDIDIK TOLERANSI BERAGAMA DI PROVINSI BANGKA BELITUNG) - Suparta Suparta (Scientia: Jurnal Hasil Penelitian, 2022)
Bangka Belitung, including a new province that was established in 2000, was designated as the 31st province by the Government of the Republic of Indonesia based on Law no. 27 of 2000 concerning the Establishment of the Bangka Belitung Archipelago Province with the capital city of Pangkalpinang and has 7 regencies. Even though it is classified as a small province, this province has various ethnic, religious and customary diversity. The existing ethnic groups are the Malays (native ethnic group), Javanese, Sundanese, Bugis, Banten, Banjar, Madurese, Palembang, Minang, Aceh, Flores, Maluku, Manado and China (about 30%). For religion in Bangka Belitung, there are all religions in Indonesia, Islam is 81.83%, Buddhism is 8.71%, Confucianism is 5.11%, Christianity is 2.44%, Catholicism is 1.79%, and Hinduism is 0. 13%. Based on the results of the research, even though Bangka Belitung has various ethnic groups and adherents of different religions, it has good inter-religious harmony, disputes and hate speech are rare, and there has never been violence, bullying or even fighting. This proves that Bangka Belitung has an attitude of tolerance that can be used as an example for other provinces. Based on the results of the researcher's analysis, the main factor causing the harmonious harmony of religions in this province is the very important and strategic role of their respective religious leaders. Religious leaders have their own strategies in educating their followers to have a high sense of tolerance towards other religions. Of course, the strategy carried out in each religion also refers to the teachings of their respective holy books which instruct that fellow religious persons must respect, appreciate and spread peace and love so that religious life becomes safe and peaceful.